An experimental study of the machining parameters in powder mixed electric discharge machining of Al–10%SiCP metal matrix composites. (7th February 2007) - Kansal, H.K.; Singh, Sehijpal; Kumar, Pradeep
The aim of this present research is to establish optimum process conditions for Powder Mixed Electric Discharge Machining (PMEDM) of Al–10%SiCP Metal Matrix Composites (MMC) by an experimental investigation using Response Surface Methodology (RSM). Aluminium powder was suspended into the dielectric fluid of Electric Discharge Machining (EDM). A modified powder mixed dielectric circulation system was developed in the laboratory for experimentation. Relationships are developed between various input process parameters (concentration of the added aluminium powder, peak current and pulse duration) and output characteristics (Machining Rate (MR), Surface Roughness (SR)). The obtained result allowed how to find the most important parameters and determine the optimal values that maximise the MR and minimise the SR. The recommended optimal process conditions have been verified by conducting confirmation experiments.